Modeling the Formation of Professional Competence of Future Programmers Through the Development of Fundamental Knowledge and Skills (Eurasian Journal of Learning and Academic Teaching, 2022)
This article presents recommendations on the development of a model for the formation of professional competence of students in the "Computer Engineering" specialty by developing fundamental knowledge